2021
DOI: 10.1145/3418501
|View full text |Cite
|
Sign up to set email alerts
|

Joint QoS-aware and Cost-efficient Task Scheduling for Fog-cloud Resources in a Volunteer Computing System

Abstract: Volunteer computing is an Internet-based distributed computing in which volunteers share their extra available resources to manage large-scale tasks. However, computing devices in a Volunteer Computing System (VCS) are highly dynamic and heterogeneous in terms of their processing power, monetary cost, and data transferring latency. To ensure both of the high Quality of Service (QoS) and low cost for different requests, all of the available computing resources mus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…In this work, the dynamic voltage and frequency scaling (DVFS) technique is also run on each solution to save energy. Scheduling of IoT tasks with volunteer fog–cloud resources was proposed in Reference 48. First, the problem has been formulated as a mixed integer linear programming (MILP) model with the aim of optimizing the total cost of computation, communication, and delay violation.…”
Section: Related Workmentioning
confidence: 99%
“…In this work, the dynamic voltage and frequency scaling (DVFS) technique is also run on each solution to save energy. Scheduling of IoT tasks with volunteer fog–cloud resources was proposed in Reference 48. First, the problem has been formulated as a mixed integer linear programming (MILP) model with the aim of optimizing the total cost of computation, communication, and delay violation.…”
Section: Related Workmentioning
confidence: 99%
“…Louail et al 30 designed and suggested a dynamic task scheduling approach for FNs in industrial IoT (IIoT) for smart factories aimed at minimizing the frequency of tasks and limiting the deadline based on the frequency of task‐performing. Hoseiny et al 31 proposed two efficient heuristic algorithms to minimize computational and communications costs as well as deadline violations in the systems of volunteer fog‐cloud computing. Almutairi and Aldossary 32 developed and suggested a fuzzy logic‐based approach for scheduling loaded tasks in cloud‐edge environments aimed at minimizing the overall service time of latency‐sensitive applications.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The number of the members of set Prob i = {P i 1 , P i 2 , … , P i m } is also equal to the number of FNs. The received task can be sent to each of the nodes with a known probability rate, and according to Equation (31), the sum of the probabilities of the actions is equal to 1 where P m represents the probability of action m, and m is a subset of actions that exist in set 𝜑.…”
Section: F I G U R Ementioning
confidence: 99%
“…Cloud and fog nodes have different processing power values measured in MIPS, memory capacity values measured in Megabytes (MB), bandwidth values measured in Megabytes Per Second (MBPS), and resource usage costs represented in Grid Dollars (G$). G$ is a currency unit used in the simulation to substitute for real money using a predefined ratio [2,35]. The virtual charge can be easily mapped to any pricing model ( 18)…”
Section: Experimental Settingsmentioning
confidence: 99%